2010
DOI: 10.1002/ajim.20851
|View full text |Cite
|
Sign up to set email alerts
|

Improving the quality of industry and occupation data at a central cancer registry

Abstract: Statewide training to highlight the importance of I/O data is an effective method to improve I/O data quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 12 publications
1
15
0
2
Order By: Relevance
“…Several years before the Comparative Effectiveness Research project, the New Hampshire State Cancer Registry provided statewide training to support better capture of I&O data, and found that I&O data quality could be “substantially improved by means of minimal training provided to cancer registrars to highlight the importance of these data.” 15 The increased capture of I&O data highlighted by the New Hampshire study was also seen in the results from this study.…”
Section: | Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Several years before the Comparative Effectiveness Research project, the New Hampshire State Cancer Registry provided statewide training to support better capture of I&O data, and found that I&O data quality could be “substantially improved by means of minimal training provided to cancer registrars to highlight the importance of these data.” 15 The increased capture of I&O data highlighted by the New Hampshire study was also seen in the results from this study.…”
Section: | Discussionsupporting
confidence: 66%
“…As shown in the New Hampshire study, cancer registrars could improve their ability to routinely capture I&O data through training on standardization of placement of this information within the medical record. 15 Additionally, successful incorporation of I&O as structured data in electronic health records could improve the data available for use in registries. Improvements in the NIOCCS tool could help registries to more easily and quickly convert I&O text into usable code.…”
Section: | Discussionmentioning
confidence: 99%
“…In a 2009 survey, only 16 states voluntarily collected information on parental occupation on birth certificates and 24 collected information on parental occupation on fetal death certificates [Fitzgerald et al, ]. Even when occupational information is collected, it is often incomplete or of poor quality [Shaw et al, ; Brender et al, ]—though the quality of information can be greatly improved when staff are trained on the importance of occupational data [Armenti et al, ]. The lack of information on parental employment status or occupation has limited research on employment and pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…A study of I&O availability (categorizing “retired” and “non‐working” as available) in the New Hampshire State Cancer Registry found differences by demographic characteristics and by broad groupings of malignancy type and data source . The current project extends this area of research by focusing on codability of I&O text to Census 2010 I&O codes by malignancy type and by demographic, source reporting, and payor characteristics.…”
Section: Introductionmentioning
confidence: 85%
“…Results of the current study show that such cases have markedly greater I&O codability when hospital records are also available and accessed for case information. A New Hampshire study showed a decrease in the number of records judged to have no I&O data from 74% to 14% after detailed records review followed by targeted registrar training in I/O collection . The percentage of records judged to have complete, codable I&O data was only 48% even after review training (in part because 20% of records belonged to individuals not in the paid workforce), but this was nearly triple the level before these additional steps.…”
Section: Discussionmentioning
confidence: 99%